Bi- and trinuclear coinage metal complexes of a PNNP ligand featuring metallophilic interactions and an unusual charge separation. Issue 38 (3rd September 2021) - Dahlen, Milena; Kehry, Max; Lebedkin, Sergei; Kappes, Manfred M.; Klopper, Wim; Roesky, Peter W.
Abstract : Homometallic bi- and trinuclear complexes of Cu, Ag and Au ligated by a tetradentate PNNP ligand are shown. Photoluminescence and theoretical studies revealed a MLCT character upon UV excitation and complemented this work. Abstract : A selective synthesis of bi- and trinuclear complexes featuring a tetradentate monoanionic PNNP ligand is presented. The binuclear coinage metal complexes show a typical fourfold coordination for Cu and Ag, which changes to a bifold coordination for Au. The latter is accompanied by an unusual charge separation. Optical properties are investigated using photoluminescence spectroscopy and complemented by time-dependent density-functional-theory calculations. All compounds demonstrate clearly distinguished features dependent on the metals chosen and differences in the complex scaffold.